Detection methods for influenza A H1N1 virus with special reference to biosensors: a review. Issue 2 (4th February 2020) - Ravina,; Dalal, Anita; Mohan, Hari; Prasad, Minakshi; Pundir, C.S.
Abstract: H1N1 (Swine flu) is caused by influenza A virus, which is a member of Orthomyxoviridae family. Transmission of H1N1 occurs from human to human through air or sometimes from pigs to humans. The influenza virus has different RNA segments, which can reassert to make new virus strain with the possibility to create an outbreak in unimmunized people. Gene reassortment is a process through which new strains are emerging in pigs, as it has specific receptors for both human influenza and avian influenza viruses. H1N1 binds specifically with an α-2, 6 glycosidic bond, which is present in human respiratory tract cells as well as in pigs. Considering the fact of fast multiplication of viruses inside the living cells, rapid detection methods need an hour. Currently, WHO recommended methods for the detection of swine flu include real-time PCR in specific testing centres that take 3–4 h. More recently, a number of methods such as Antigen–Antibody or RT-LAMP and DNA biosensors have also been developed that are rapid and more sensitive. This review describes the various challenges in the diagnosis of H1N1, and merits and demerits of conventional vis-à-vis latest methods with special emphasis on biosensors.